Analyse De La Promotion Du Genre Et De L’équité Dans Le Processus Du Développement Local : Cas Du PDC De La Commune De Matamèye - Aboubacar, Zakari (European Scientific Journal, ESJ, 2017)
This study aims is to identify the level of integration of the female component in development actions at the level of the urban commune of Matamèye. It is based on an exploitation of the field data with the help of a maintenance guide, a questionnaire and the support of the Municipal Development Plan. The interview took place in the semi-structured form. It is clear that there are more than a hundred registered women’s groups both in the commune and in the departmental service. These groups operate in the following activities: extraction of peanut oil, market gardening, manufacture of traditional spaghetti and garin yara. The promoters of these activities do not complain. Indeed, even if these results do not live up to expectations, we must encourage the initiatives of the municipality which try with little means to create a framework that allows these structures to evolve in complete independence. Nevertheless, there are conflicts of jurisdiction in the granting of official authorization to these groups between the supervisory authority and the newly elected administration. Each of the two parties believes that it is up to the municipality to issue them according to the local authorities code according to the ordinance n ° 2010-54 of 17 September 2010. That is why we say that the conflicts of competence between the supervisory authority and the newly elected government that often appear must not hamper local development actions, the principle for which decentralization has emerged.